The Subcellular Proteome of a Planctomycetes Bacterium Shows That Newly Evolved Proteins Have Distinct Fractionation Patterns - Seeger, Christian; Dyrhage, Karl; Mahajan, Mayank; Odelgard, Anna; Lind, Sara Bergström; Andersson, Siv G. E. (Frontiers in Microbiology, 2021)
The Planctomycetes bacteria have unique cell architectures with heavily invaginated membranes as confirmed by three-dimensional models reconstructed from FIB-SEM images of Tuwongella immobilis and Gemmata obscuriglobus. The subcellular proteome of T. immobilis was examined by differential solubilisation followed by LC-MS/MS analysis, which identified 1569 proteins in total. The Tris-soluble fraction contained mostly cytoplasmic proteins, while inner and outer membrane proteins were found in the Triton X-100 and SDS-soluble fractions, respectively. For comparison, the subcellular proteome of Escherichia coli was also examined using the same methodology. A notable difference in the overall fractionation pattern of the two species was a 5-fold higher number of cytoplasmic proteins in the SDS-soluble fraction in T. immobilis. One category of such proteins is represented by innovations in the Planctomycetes lineage, including unique sets of serine/threonine kinases and extracytoplasmic sigma factors with WD40 repeat domains for which no homologs are present in E. coli. Other such proteins are members of recently expanded protein families in which the newly evolved paralog with a new domain structure is recovered from the SDS-soluble fraction, while other paralogs may have similar domain structures and fractionation patterns as the single homolog in E. coli. The expanded protein families in T. immobilis include enzymes involved in replication-repair processes as well as in rRNA and tRNA modification and degradation. These results show that paralogization and domain shuffling have yielded new proteins with distinct biochemical characteristics. Understanding the molecular intricacies of these adaptive changes might aid in the development of a model for the evolution of cellular complexity.